Clinical outcomes of lithium disilicate single crowns after a mean duration of 3 years - A retrospective study - Samer, Mazin Saleh; Ali, Tara Bai Taiyeb; Abdullah, Hadijah (Quintessence Publishing, 2018)
Purpose: To investigate the clinical performance and clinical survival rate of lithium disilicate-based core ceramic (IPS e.max Press) utilised in single crowns and to the accompanying periodontal health status. Materials and Methods: A total of 47 patients with 88 IPS e.max Press single crowns were examined at the Faculty of Dentistry, University of Malaya, using modified United States Public Health Service evaluation criteria (USPHS). These 88 crowned teeth included 19 vital and 69 nonvital teeth that were restored with different post and core materials. The periodontal status was compared using the plaque index (PI), gingival recession (GR), modified papillary bleeding index (MPBI) and probing pocket depth (PPD) between the crowned teeth and contralateral control (sound) teeth. Results: About 96.6% of the crowns exhibited satisfactory clinical performance. The mean survival rate at three years was 97.7%, and 100% at two years with a low incidence of fractures. There were no staitistically significant differences in the mean gingival recession (p = 0.182) and mean plaque scores (p = 0.102) between crowned and control teeth. The crowned teeth had higher mean MPBI (p = 0.000) and PPD (p = 0.051) compared to the contralateral sound teeth. Periodontal response in relation to subgingival crown margins, was statistically significantly lower regarding pocket depths (p = 0.01) and bleeding on probing (p = 0.00). Conclusion: IPS e.max Press crowns exhibited satisfactory clinical performance with high survival rate. No dentinal sensitivity was recorded. Plaque retention and gingival recession were similar to contralateral control teeth. Poor periodontal health was related to the subgingival crown margins.